Analisis Faktor-Faktor Yang Mempengaruhi Permintaan Audit: KPRI Kabupaten Lumajang - Oyong Lisa (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2011)
The main objective of this study is to examine factors to influence audit demand to KPRI in the central Java. These factors are sum of members, size, cost of audit, sum of debit, and management perception. Data were collected from 150 Manajer of broad of cooperative KPRI in Lumajang and in sub-district with random sampling. The hypothesis was analysed using logistic regression. The result shows that variables sum of members, sum of debt and management perception were significantly to influence audit demand to KPRI. These variables size and cost audit were not significantly to influence audit demand to KPRI.